Bio-based core-shell structure acrylic pressure-sensitive adhesive and preparation method thereof

By using lignin as a bio-based monomer, a bio-based core-shell structure acrylic pressure-sensitive adhesive is prepared, which solves the problem of difficult decomposition of existing aqueous acrylic pressure-sensitive adhesives, and realizes environmentally friendly and renewable high-performance pressure-sensitive adhesives.

CN119463759APending Publication Date: 2025-02-18ZHEJIANG SATELLITE PETRO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411813444.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing aqueous acrylic pressure-sensitive adhesives are mainly produced by petrochemical resources, and are difficult to decompose in the environment and cannot meet higher environmental protection requirements.

Method used

Using lignin as a bio-based monomer, a bio-based core-shell structure acrylic pressure-sensitive adhesive is prepared through high-pressure reaction and multi-step process, combining soft monomers, hard monomers and other additives to form a hard core soft shell structure.

Benefits of technology

It realizes environmentally friendly and renewable pressure-sensitive adhesive, which has the same properties as traditional water-based acrylic pressure-sensitive adhesive, including excellent initial adhesion, peel strength and stickiness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention aims to provide the bio-based core-shell structure acrylic pressure-sensitive adhesive and the preparation method thereof, and the lignin bio-based monomer is introduced, so that the adhesive has the advantages of environmental protection and reproducibility. The cohesive force of the polymer is ensured, the sufficient wetting ability and viscosity are also ensured, and the adhesive has excellent initial adhesion, peel strength and persistent adhesivity. The film has the characteristics of convenience in use and good environmental friendliness, can be improved by a user according to different requirements, and can be widely applied to the fields of packaging, advertisements, protective films, transportation, electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention relates to the field of adhesive technology, specifically to the preparation of a bio-based core-shell structure acrylic pressure-sensitive adhesive. Background Art

[0002] Pressure-sensitive adhesive is a special adhesive that can adhere to the surface of various materials under slight pressure. Pressure-sensitive adhesive is widely used in labels, tapes, protective films, medical supplies and other fields. In order to meet the increasing demand for environmental protection, water-based acrylic pressure-sensitive adhesive has attracted more and more attention due to its non-toxicity. However, water-based acrylic pressure-sensitive adhesive is still dominated by polymers produced from petrochemical resources and is difficult to decompose in the environment. Using renewable resources to obtain high-performance pressure-sensitive adhesives will definitely become the future direction of the industry.

[0003] Lignin is a large, easily available renewable resource that is widely found in agricultural residues and by-products of pulp and papermaking processes. Using lignin to develop environmentally friendly, renewable and degradable pressure-sensitive adhesives is a meaningful study.

[0004] The prior art discloses CN113136055A A 20210720, a packaging material based on biodegradable technology: The present invention discloses a packaging material based on biodegradable technology, comprising the following raw materials in parts by weight: 15-25 parts of polyvinyl alcohol, 8-12 parts of modified nano calcium carbonate, 20-30 parts of starch, 8-10 parts of lignin, 3-6 parts of dispersant, and 3-5 parts of plasticizer. The present invention uses polyvinyl alcohol and starch as the main components of the packaging material. The non-toxic and harmless polyvinyl alcohol has a high crystallinity and a certain mechanical strength. The starch is widely available, low-priced, environmentally friendly and renewable, and can be compatible with polyvinyl alcohol. It has the advantages of environmental protection, degradation and cost saving. In addition, modified nano calcium carbonate is added as an inorganic filler to enhance the tensile strength of the packaging material. The nano calcium carbonate is surface modified by a high temperature resistant silane coupling agent, which not only solves the problem of compatibility between the inorganic filler and the organic matrix, but also brings the packaging material high temperature resistance by virtue of the thermal stability of the silane coupling agent. CN115537155A A 20221230A removable acrylate pressure-sensitive adhesive with high peel strength and preparation method thereof: A removable acrylate pressure-sensitive adhesive with high peel strength, comprising the following components by mass: 60-98 parts of soft elastomer, 0-30 parts of hard monomer, 0.1-5 parts of functional monomer, 0.2-2 parts of emulsifier, 0.1-0.5 parts of buffer, 0.1-0.8 parts of thermal initiator, 0.1-0.5 parts of oxidant, 0.1-0.3 parts of reducing agent, 0.1-2 parts of pH value regulator, 1-30 parts of rosin emulsion, 40-70 parts of deionized water. The present invention also provides a method for preparing a removable acrylate pressure-sensitive adhesive with high peel strength. The pressure-sensitive adhesive prepared by the above raw materials and methods has the advantages of high peel strength and high cohesive strength, high initial peel strength, small peel force growth, no residual adhesive after peeling, etc., and can be adapted to a variety of substrates and application scenarios. While the above mentioned methods are not green or need to be further developed, the lignin of the present invention is an agricultural residue and exists in the by-products of pulp and paper making processes, and thus belongs to waste utilization.

[0005] Therefore, the present invention focuses on developing a bio-based core-shell acrylic pressure-sensitive adhesive, which makes full use of lignin bio-based monomers, which helps to meet higher environmental protection requirements. At the same time, the bio-based pressure-sensitive adhesive provided by the present invention is a hard core soft shell structure, and has comparable performance to traditional water-based acrylic pressure-sensitive adhesives. Summary of the invention

[0006] The purpose of the present invention is to provide a bio-based core-shell acrylic pressure-sensitive adhesive, which helps to meet higher environmental protection requirements. The bio-based pressure-sensitive adhesive provided by the present invention is a hard core soft shell structure, and has comparable performance to traditional water-based acrylic pressure-sensitive adhesives.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] On the one hand, the present invention provides a bio-based core-shell structure acrylic pressure-sensitive adhesive, comprising the following components in parts by weight: 10-250 parts of lignin bio-based monomer, 10-250 parts of soft monomer, 0-5 parts of hard monomer, 0.1-5 parts of pH buffer, 1-10 parts of emulsifier, 0.1-0.5 parts of chain transfer agent, 1-10 parts of silane coupling agent, 1-10 parts of initiator, 0.1-5 parts of oxidant, 0.1-5 parts of reducing agent, and 500-1000 parts of deionized water.

[0009] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the soft monomer is one or more of butyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate.

[0010] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the hard monomer is one or more of styrene and methyl methacrylate.

[0011] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the pH buffer is one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.

[0012] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the emulsifier is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and sodium rosin acid.

[0013] Furthermore, the bio-based core-shell acrylic pressure-sensitive adhesive is characterized in that the chain transfer agent is dodecyl mercaptan.

[0014] Furthermore, the bio-based core-shell acrylic pressure-sensitive adhesive is characterized by comprising one or more of the silane coupling agents A-171, KH-550, KH-560, and KH-570.

[0015] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the initiator is one or more of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0016] Furthermore, the bio-based core-shell structure acrylic pressure-sensitive adhesive is characterized in that the oxidant is tert-butyl hydroperoxide, and the reducing agent is one or more of bleaching powder, sodium sulfite, sodium bisulfite, and sodium metabisulfite.

[0017] In another aspect, the present invention provides a method for preparing a bio-based core-shell acrylic pressure-sensitive adhesive, comprising the following steps:

[0018] (1) Preparation of lignin bio-based monomers:

[0019] a. Add lignin, methanol and ruthenium carbon catalyst to a high-pressure reactor with heating and ventilation pressurization functions. Purge the reactor with H2 three times and then pressurize it with H2 to a pressure of 40 bar. Heat the reactor to 250°C and stir for 15 hours. After the reaction is completed, cool the reactor to room temperature with an external compressed air flow. Filter to separate the solid and liquid. Wash the solid with methanol and combine the washing liquid with the filtrate. Use a rotary evaporator to remove methanol at 60°C and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde.

[0020] b. The mixture obtained in the above step and ethylene carbonate are placed in a reaction apparatus equipped with a reflux condenser and equipped with ventilation, heating and stirring functions, and stirred and mixed under argon. Then the apparatus is immersed in an oil bath set at 150°C. After the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 1,5-diazabicyclo[4.3.0]-5-nonene is injected into the reaction mixture. The reaction is carried out at 150°C for 30 minutes, and then the oil bath temperature is raised to 180°C. The reaction is continued for 4 hours. The product is dissolved in dichloromethane and extracted twice with deionized water to remove the residue of ethylene carbonate. The organic phase is dried with Na2SO4 and filtered through silica gel to remove the residue of salts.

[0021] c. The product obtained in the above steps was dissolved in dichloromethane. Triethylamine was added and sealed. The mixture was purged with argon for 15 minutes and then immersed in an ice bath. Methacrylic anhydride was added dropwise to the solution within 10 minutes. The reaction was carried out at room temperature for 18 hours. The final mixture was washed three times with 0.05M NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase was dried with Na2SO4, filtered, and the solvent was removed in vacuo at 30°C. Finally, the product was purified using a 9:1 mixture of cyclohexane and ethyl acetate. (2) 10wt% deionized water and 20wt% emulsifier were added to a stirring container with a stirring device and a feed port, and stirring was started at a frequency of 40Hz. After sufficient stirring for 10 minutes, 20wt% lignin bio-based monomer, all hard monomers and 10wt% initiator were added, and stirring was continued for 30 minutes for standby use.

[0022] (3) Add 30 wt% of deionized water and the remaining 80 wt% of emulsifier into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add the remaining 80 wt% of lignin bio-based monomer, all soft monomers, chain transfer agent, silane coupling agent and 30 wt% of initiator, and continue stirring for 30 minutes for use.

[0023] (4) Add 60% of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add the above-mentioned pH buffer and continue to heat. When the temperature rises to 75°C, add 60% of the above-mentioned initiator and continue to heat.

[0024] (5) When the temperature in the reaction device rises to 84°C, start dripping the mixed emulsion in the stirring container of step (2) into the reaction device. The dripping time is 1h-1.5h, and the temperature is maintained at 84±1°C during the dripping process.

[0025] A core structure polymer emulsion is obtained.

[0026] (6) When the step (5) is finished, the mixed emulsion in the stirring container of step (3) is added dropwise into the reaction device. The addition time is 2h-2.5h, and the temperature is maintained at 84±1°C during the addition process. A core-shell structure polymer emulsion is obtained.

[0027] (7) After the step (6) is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept, the temperature is lowered to 70-75°C, the oxidant is added, and the reducing agent is added after stirring for 20 minutes. The temperature is further lowered after stirring for 20 minutes. The temperature is lowered to 45°C and the material is discharged.

[0028] The beneficial effects of the present invention are:

[0029] 1. Existing water-based acrylic pressure-sensitive adhesive products are petrochemical resource polymers that are difficult to decompose in the environment. This product introduces bio-based materials and has the advantages of being environmentally friendly and renewable.

[0030] 2. The invention provides a pressure-sensitive adhesive with a hard-core and soft-shell structure, which not only ensures the cohesion of the polymer, but also ensures sufficient wetting ability and viscosity, and has excellent initial adhesion, peel strength and sustained adhesion performance.

[0031] 3. The invention is easy to use and environmentally friendly. Users can improve it according to different needs. It can be widely used in packaging, advertising, protective film, transportation, electronics and other fields. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are further described below in conjunction with the examples.

[0033] A bio-based core-shell acrylic pressure-sensitive adhesive, characterized by the following preparation steps:

[0034] (1) Preparation of lignin bio-based monomers:

[0035] a. By weight fraction, 10 parts of lignin, 160 parts of methanol and 1 part of ruthenium carbon catalyst are added to a high-pressure reactor with heating and ventilation pressurization functions. The reactor is purged with H2 three times and then pressurized to a pressure of 40 bar with H2. The reactor is heated to 250°C and stirred for 15 hours. After the reaction is completed, the reactor is cooled to room temperature with an external compressed air flow. Filter to separate the solid and liquid. Wash the solid with 80 parts of methanol, and combine the washing liquid with the filtrate. Use a rotary evaporator to remove methanol at 60°C, and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde.

[0036] b. 80 parts of the mixture obtained in the above step and 50 parts of ethylene carbonate are placed in a reaction apparatus equipped with ventilation, heating and stirring functions and equipped with a reflux condenser, and mixed under argon and high magnetic stirring. Then immerse the apparatus in an oil bath set at 150°C. After the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 0.2 parts of 1,5-diazabicyclo[4.3.0]-5-nonene are injected into the reaction mixture. The reaction is carried out at 150°C for 30 minutes, and then the oil bath temperature is raised to 180°C. The reaction is continued for 4 hours. The product is dissolved in dichloromethane and extracted twice with deionized water to remove the residues of ethylene carbonate. The organic phase is dried over Na2SO4 and filtered through silica gel to remove the residues of salts.

[0037] c. 80 parts of the mixture obtained in the above steps were dissolved in 90 parts of dichloromethane. 70 parts of triethylamine were added and sealed. The mixture was purged with argon for 15 minutes and then immersed in an ice bath. 80 parts of methacrylic anhydride were added dropwise to the solution within 10 minutes. The reaction was carried out at room temperature for 18 hours. The final mixture was washed three times with 0.05M NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase was dried with Na2SO4, filtered, and the solvent was removed in vacuo at 30°C. Finally, the product was purified using a 9:1 mixture of cyclohexane and ethyl acetate.

[0038] (2) Add 50 parts of deionized water and 1 part of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add 30 parts of the lignin bio-based monomer obtained in step (1), 5 parts of methyl methacrylate and 0.4 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0039] (3) Add 150 parts of deionized water and 4 parts of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring at a stirring frequency of 40 Hz. After stirring for 10 minutes, add the remaining 120 parts of lignin bio-based monomer, 250 parts of butyl acrylate, 0.3 parts of dodecyl mercaptan, 3 parts of A-171 and 1.2 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0040] (4) Add 350 parts of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add 0.5 parts of sodium bicarbonate and continue to heat. When the temperature rises to 75°C, add 2.4 parts of ammonium persulfate and continue to heat.

[0041] (5) When the temperature in the reaction device rises to 84°C, start dripping the mixed emulsion in the stirring container of step (2) into the reaction device. The dripping time is 1h-1.5h, and the temperature is maintained at 84±1°C during the dripping process.

[0042] (6) When the step (5) is finished, the mixed emulsion in the stirring container of step (3) is added dropwise into the reaction device. The addition time is 2h-2.5h, and the temperature is maintained at 84±1°C during the addition process.

[0043] (7) After the addition is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept at 70-75°C, 0.5 parts of tert-butyl hydroperoxide are added, and after stirring for 20 minutes, 0.5 parts of bleaching powder are added. After stirring for 20 minutes, the temperature is further lowered. The temperature is lowered to 45°C and the material is discharged.

[0044] Example 2

[0045] Compared with Example 1, the silane coupling agent A-171 in step (3) is replaced with KH570.

[0046] A bio-based core-shell acrylic pressure-sensitive adhesive, characterized by the following preparation steps:

[0047] (1) Preparation of lignin bio-based monomers:

[0048] a. By weight fraction, 10 parts of lignin, 160 parts of methanol and 1 part of ruthenium carbon catalyst are added to a high-pressure reactor with heating and ventilation pressurization functions. The reactor is purged with H2 three times and then pressurized to a pressure of 40 bar with H2. The reactor is heated to 250°C and stirred for 15 hours. After the reaction is completed, the reactor is cooled to room temperature with an external compressed air flow. Filter to separate the solid and liquid. Wash the solid with 80 parts of methanol, and combine the washing liquid with the filtrate. Use a rotary evaporator to remove methanol at 60°C, and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde.

[0049] b. 80 parts of the mixture obtained in the above step and 50 parts of ethylene carbonate are placed in a reaction apparatus equipped with ventilation, heating and stirring functions and equipped with a reflux condenser, and mixed under argon and high magnetic stirring. Then immerse the apparatus in an oil bath set at 150°C. After the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 0.2 parts of 1,5-diazabicyclo[4.3.0]-5-nonene are injected into the reaction mixture. The reaction is carried out at 150°C for 30 minutes, and then the oil bath temperature is raised to 180°C. The reaction is continued for 4 hours. The product is dissolved in dichloromethane and extracted twice with deionized water to remove the residues of ethylene carbonate. The organic phase is dried over Na2SO4 and filtered through silica gel to remove the residues of salts.

[0050] c. 80 parts of the mixture obtained in the above steps were dissolved in 90 parts of dichloromethane. 70 parts of triethylamine were added and sealed. The mixture was purged with argon for 15 minutes and then immersed in an ice bath. 80 parts of methacrylic anhydride were added dropwise to the solution within 10 minutes. The reaction was carried out at room temperature for 18 hours. The final mixture was washed three times with 0.05M NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase was dried with Na2SO4, filtered, and the solvent was removed in vacuo at 30°C. Finally, the product was purified using a 9:1 mixture of cyclohexane and ethyl acetate.

[0051] (2) Add 50 parts of deionized water and 1 part of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add 30 parts of the lignin bio-based monomer obtained in step (1), 5 parts of methyl methacrylate and 0.4 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0052] (3) Add 150 parts of deionized water and 4 parts of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add the remaining 120 parts of lignin bio-based monomer, 250 parts of butyl acrylate, 0.3 parts of dodecyl mercaptan, 3 parts of KH570 and 1.2 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0053] (4) Add 350 parts of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add 0.5 parts of sodium bicarbonate and continue to heat. When the temperature rises to 75°C, add 2.4 parts of ammonium persulfate and continue to heat.

[0054] (5) When the temperature in the reaction device rises to 84°C, start dripping the mixed emulsion in the stirring container of step (2) into the reaction device. The dripping time is 1h-1.5h, and the temperature is maintained at 84±1°C during the dripping process.

[0055] (6) When the step (5) is finished, the mixed emulsion in the stirring container of step (3) is added dropwise into the reaction device. The addition time is 2h-2.5h, and the temperature is maintained at 84±1°C during the addition process.

[0056] (7) After the addition is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept at 70-75°C, 0.5 parts of tert-butyl hydroperoxide are added, and after stirring for 20 minutes, 0.5 parts of bleaching powder are added. After stirring for 20 minutes, the temperature is further lowered. The temperature is lowered to 45°C and the material is discharged.

[0057] Example 3

[0058] Compared with Example 1, the amount of chain transfer agent dodecyl mercaptan used in step 3 is reduced.

[0059] A bio-based core-shell acrylic pressure-sensitive adhesive, characterized by the following preparation steps:

[0060] (1) Preparation of lignin bio-based monomers:

[0061] a. By weight fraction, 10 parts of lignin, 160 parts of methanol and 1 part of ruthenium carbon catalyst are added to a high-pressure reactor with heating and ventilation pressurization functions. The reactor is purged with H2 three times and then pressurized to a pressure of 40 bar with H2. The reactor is heated to 250°C and stirred for 15 hours. After the reaction is completed, the reactor is cooled to room temperature with an external compressed air flow. Filter to separate the solid and liquid. Wash the solid with 80 parts of methanol, and combine the washing liquid with the filtrate. Use a rotary evaporator to remove methanol at 60°C, and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde.

[0062] b. 80 parts of the mixture obtained in the above step and 50 parts of ethylene carbonate are placed in a reaction apparatus equipped with ventilation, heating and stirring functions and equipped with a reflux condenser, and mixed under argon and high magnetic stirring. Then immerse the apparatus in an oil bath set at 150°C. After the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 0.2 parts of 1,5-diazabicyclo[4.3.0]-5-nonene are injected into the reaction mixture. The reaction is carried out at 150°C for 30 minutes, and then the oil bath temperature is raised to 180°C. The reaction is continued for 4 hours. The product is dissolved in dichloromethane and extracted twice with deionized water to remove the residues of ethylene carbonate. The organic phase is dried over Na2SO4 and filtered through silica gel to remove the residues of salts.

[0063] c. 80 parts of the mixture obtained in the above steps were dissolved in 90 parts of dichloromethane. 70 parts of triethylamine were added and sealed. The mixture was purged with argon for 15 minutes and then immersed in an ice bath. 80 parts of methacrylic anhydride were added dropwise to the solution within 10 minutes. The reaction was carried out at room temperature for 18 hours. The final mixture was washed three times with 0.05M NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase was dried with Na2SO4, filtered, and the solvent was removed in vacuo at 30°C. Finally, the product was purified using a 9:1 mixture of cyclohexane and ethyl acetate.

[0064] (2) Add 50 parts of deionized water and 1 part of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add 30 parts of the lignin bio-based monomer obtained in step (1), 5 parts of methyl methacrylate and 0.4 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0065] (3) Add 150 parts of deionized water and 4 parts of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring at a stirring frequency of 40 Hz. After stirring for 10 minutes, add the remaining 120 parts of lignin bio-based monomer, 250 parts of butyl acrylate, 0.1 parts of dodecyl mercaptan, 3 parts of A-171 and 1.2 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0066] (4) Add 350 parts of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add 0.5 parts of sodium bicarbonate and continue to heat. When the temperature rises to 75°C, add 2.4 parts of ammonium persulfate and continue to heat.

[0067] (5) When the temperature in the reaction device rises to 84°C, start dripping the mixed emulsion in the stirring container of step (2) into the reaction device. The dripping time is 1h-1.5h, and the temperature is maintained at 84±1°C during the dripping process.

[0068] (6) When the step (5) is finished, the mixed emulsion in the stirring container of step (3) is added dropwise into the reaction device. The addition time is 2h-2.5h, and the temperature is maintained at 84±1°C during the addition process.

[0069] (7) After the addition is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept at 70-75°C, 0.5 parts of tert-butyl hydroperoxide are added, and after stirring for 20 minutes, 0.5 parts of bleaching powder are added. After stirring for 20 minutes, the temperature is further lowered. The temperature is lowered to 45°C and the material is discharged.

[0070] Comparative Example 1

[0071] Compared with Example 1, this comparative example does not use lignin bio-based monomers, but replaces them with butyl acrylate. An acrylic pressure-sensitive adhesive, characterized by the following preparation steps:

[0072] (1) Add 50 parts of deionized water and 1 part of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring at a stirring frequency of 40 Hz. After stirring thoroughly for 10 minutes, add 30 parts of butyl acrylate, 5 parts of methyl methacrylate and 0.4 parts of ammonium persulfate, and continue stirring for 30 minutes for standby use.

[0073] (2) Add 150 parts of deionized water and 4 parts of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring at a stirring frequency of 40 Hz. After stirring for 10 minutes, add the remaining 370 parts of butyl acrylate, 0.1 parts of dodecyl mercaptan, 3 parts of A-171 and 1.2 parts of ammonium persulfate, and continue stirring for 30 minutes for standby use.

[0074] (3) Add 350 parts of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add 0.5 parts of sodium bicarbonate and continue to heat. When the temperature rises to 75°C, add 2.4 parts of ammonium persulfate and continue to heat.

[0075] (4) When the temperature in the reaction device rises to 84°C, start dripping the mixed emulsion in the stirring container of step (1) into the reaction device. The dripping time is 1h-1.5h, and the temperature is maintained at 84±1°C during the dripping process.

[0076] (5) When the step (4) is finished, the mixed emulsion in the stirring container of step (2) is added dropwise into the reaction device. The addition time is 2h-2.5h, and the temperature is maintained at 84±1°C during the addition process.

[0077] (6) After the addition is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept at 70-75°C, 0.5 parts of tert-butyl hydroperoxide are added, and after stirring for 20 minutes, 0.5 parts of bleaching powder are added. After stirring for 20 minutes, the temperature is further lowered. The temperature is lowered to 45°C and the material is discharged.

[0078] Comparative Example 2

[0079] Compared with Example 1, this comparative example is not divided into two stages of dropwise addition, and the polymer does not form a core-shell structure.

[0080] An acrylic pressure-sensitive adhesive, characterized by comprising the following preparation steps:

[0081] (1) Preparation of lignin bio-based monomers:

[0082] a. By weight fraction, 10 parts of lignin, 160 parts of methanol and 1 part of ruthenium carbon catalyst are added to a high-pressure reactor with heating and ventilation pressurization functions. The reactor is purged with H2 three times and then pressurized to a pressure of 40 bar with H2. The reactor is heated to 250°C and stirred for 15 hours. After the reaction is completed, the reactor is cooled to room temperature with an external compressed air flow. Filter to separate the solid and liquid. Wash the solid with 80 parts of methanol, and combine the washing liquid with the filtrate. Use a rotary evaporator to remove methanol at 60°C, and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde.

[0083] b. 80 parts of the mixture obtained in the above step and 50 parts of ethylene carbonate are placed in a reaction apparatus equipped with ventilation, heating and stirring functions and equipped with a reflux condenser, and mixed under argon and high magnetic stirring. Then immerse the apparatus in an oil bath set at 150°C. After the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 0.2 parts of 1,5-diazabicyclo[4.3.0]-5-nonene are injected into the reaction mixture. The reaction is carried out at 150°C for 30 minutes, and then the oil bath temperature is raised to 180°C. The reaction is continued for 4 hours. The product is dissolved in dichloromethane and extracted twice with deionized water to remove the residues of ethylene carbonate. The organic phase is dried over Na2SO4 and filtered through silica gel to remove the residues of salts.

[0084] c. 80 parts of the mixture obtained in the above steps were dissolved in 90 parts of dichloromethane. 70 parts of triethylamine were added and sealed. The mixture was purged with argon for 15 minutes and then immersed in an ice bath. 80 parts of methacrylic anhydride were added dropwise to the solution within 10 minutes. The reaction was carried out at room temperature for 18 hours. The final mixture was washed three times with 0.05M NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase was dried with Na2SO4, filtered, and the solvent was removed in vacuo at 30°C. Finally, the product was purified using a 9:1 mixture of cyclohexane and ethyl acetate.

[0085] (2) Add 200 parts of deionized water and 5 parts of sodium dodecylbenzene sulfonate into a stirring container with a stirring device and a feeding port, start stirring, and the stirring frequency is 40 Hz. After stirring for 10 minutes, add 150 parts of the lignin bio-based monomer obtained in step (1), 250 parts of butyl acrylate, 0.1 parts of dodecyl mercaptan, 3 parts of A-171, 5 parts of methyl methacrylate and 1.6 parts of ammonium persulfate, and continue stirring for 30 minutes for use.

[0086] (3) Add 350 parts of deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, and start heating. When the temperature rises to 65°C, add 0.5 parts of sodium bicarbonate and continue to heat. When the temperature rises to 75°C, add 2.4 parts of ammonium persulfate and continue to heat.

[0087] (4) When the temperature in the reaction device rises to 84°C, start adding the mixed emulsion in the stirring container of step (2) into the reaction device. The addition time is 3.5-4 hours, and the temperature is maintained at 84±1°C during the addition process.

[0088] (5) After the addition is completed, the temperature is kept at 84±1°C for 90 minutes. After the temperature is kept at 70-75°C, 0.5 parts of tert-butyl hydroperoxide are added, and after stirring for 20 minutes, 0.5 parts of bleaching powder are added. After stirring for 20 minutes, the temperature is further lowered. The temperature is lowered to 45°C and the material is discharged.

[0089] Comparative Example 3

[0090] Compared with Example 1, 10 parts of lignin were replaced by (refer to CN113136055A 20210720) 3 parts of polyvinyl alcohol, 1.6 parts of nano calcium carbonate, 4 parts of starch, and 1.6 parts of lignin, and the rest were the same as Example 1.

[0091] Comparative Example 4

[0092] The samples of rosin / bio-based acrylate THFMA-LMA PSA obtained from the correspondence of Nanjing Forestry University were directly tested.

[0093] The pressure-sensitive adhesive polymers prepared in Examples 1-3 and Comparative Examples 1-3 were uniformly coated on a BOPP film and cured in an electric heated air drying oven at 105° C. for 4 minutes to obtain a pressure-sensitive adhesive tape with an adhesive layer thickness of 20-25 μm, and the performance of the pressure-sensitive adhesive tape was tested.

[0094] Testing: 180° peel strength was tested according to GB / T 2792-2014 (China), initial adhesion was tested according to GB / T4852-2014 (China), and sustained adhesion was tested according to GB / T 4851-2014 (China). The test results are shown in the table below:

[0095] project 180° peel strength (N / 25mm) Initial adhesion (steel ball number) Maintaining adhesive properties Example 1 9.4 19 70h Example 2 8.6 21 68h Example 3 8.1 18 92h Comparative Example 1 7.5 18 65h Comparative Example 2 6.2 15 21h Comparative Example 3 6.5 12 35h Comparative Example 4 8.5 17 69h

[0096] By comparing Examples 1-3 with Comparative Example 1, it can be seen that the performance of the bio-based core-shell structure pressure-sensitive adhesive prepared by the present invention is comparable to that of the pressure-sensitive adhesive prepared using petrochemical resources. The product introduces bio-based materials, which have the advantages of being environmentally friendly and renewable; it not only ensures the cohesion of the polymer, but also ensures sufficient wetting ability and viscosity, and has excellent initial adhesion, peel strength and sustained adhesion. By comparing Examples 1-3 with Comparative Example 2, it can be seen that the core-shell structure improves the performance of the bio-based acrylic pressure-sensitive adhesive. Moreover, compared with the bio-based core-shell structure pressure-sensitive adhesive (Comparative Examples 3-4) in existing research, the performance is comparable or slightly better.

[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A bio-based core-shell acrylic pressure-sensitive adhesive, characterized in that: The invention comprises the following components in parts by weight: lignin bio-based monomer, soft monomer, hard monomer, pH buffer, emulsifier, chain transfer agent, silane coupling agent, initiator, oxidant, reductant and deionized water.

2. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The soft monomer is one or more of butyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate.

3. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The hard monomer is one or more of styrene and methyl methacrylate.

4. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The pH buffer is one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.

5. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The emulsifier is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and sodium rosin acid.

6. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The chain transfer agent is dodecyl mercaptan.

7. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: One or more of the silane coupling agents A-171, KH-550, KH-560, and KH-570.

8. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The initiator is one or more of ammonium persulfate, sodium persulfate and potassium persulfate.

9. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The oxidizing agent is tert-butyl hydroperoxide, and the reducing agent is one or more of bleaching agent, sodium sulfite, sodium bisulfite, and sodium pyrosulfite.

10. The bio-based core-shell acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The acrylic pressure-sensitive adhesive has the following preparation steps: (1) Preparation of lignin bio-based monomers: a. Add lignin, methanol and ruthenium carbon catalyst into a high-pressure reactor with heating and ventilation pressurization functions, purge the reactor with H2, then pressurize the reactor with H2, heat the reactor, and stir it. After the reaction is completed, cool the reactor to room temperature with an external compressed air flow, filter to separate the solid and liquid, wash the solid with methanol, and combine the washing liquid with the filtrate, use a rotary evaporator to remove methanol, and extract the residue with cyclohexane to obtain a mixture rich in small molecules such as vanillin and syringaldehyde; b. The mixture obtained in the above step and ethylene carbonate are placed in a reaction device equipped with a reflux condenser and equipped with ventilation, heating and stirring functions, mixed under argon and high magnetic stirring, and then immersed in an oil bath, the temperature is set, and after the ethylene carbonate is completely melted and the reaction mixture is homogeneous, 1,5-diazabicyclo[4.3.0]-5-nonene is injected into the reaction mixture, the temperature and reaction time are set, and then the oil bath temperature is increased, and the reaction is continued for a period of time, the product is dissolved in dichloromethane and extracted twice with deionized water to remove the residue of ethylene carbonate, and the organic phase is dried with Na2SO4 and filtered through silica gel to remove the residue of salts; c. The product obtained in the above step is dissolved in dichloromethane, triethylamine is added, and the mixture is sealed. The mixture is purged with argon for a certain period of time, and then immersed in an ice bath. Methacrylic anhydride is added dropwise to the solution for a certain period of time. The reaction is carried out at room temperature for a certain period of time. The final mixture is washed three times with NaOH solution, washed twice with deionized water, and then extracted with ethyl acetate. The organic phase is dried with Na2SO4, filtered, and the solvent is removed in vacuo at a certain temperature. Finally, the product is purified using a mixture of cyclohexane and ethyl acetate; (2) Add deionized water and emulsifier into a stirring container with a stirring device and a feeding port, start stirring, add lignin bio-based monomer, all hard monomers and initiator after sufficient stirring, and continue stirring for use; (3) Add deionized water and remaining emulsifier into a stirring container with a stirring device and a feeding port, start stirring, add remaining lignin bio-based monomer, all soft monomers, chain transfer agent, silane coupling agent and initiator with sufficient stirring, and continue stirring for use; (4) adding deionized water into a reaction device equipped with a stirring device, a heating device and a dropping device, starting heating, adding the above-mentioned pH buffer when the temperature rises to 65° C., continuing to heat, adding 60% of the above-mentioned initiator when the temperature rises to 75° C., and continuing to heat; (5) When the temperature in the reaction device rises to a certain value, the mixed emulsion in the stirring container of step (2) is added dropwise into the reaction device, the dropping time is controlled, and the temperature is maintained during the dropping process to obtain a core structure polymer emulsion; (6) When the step (5) is finished, the mixed emulsion in the stirring container of step (3) is added dropwise into the reaction device, the addition time is controlled, and the temperature is maintained during the addition to obtain a core-shell structure polymer emulsion; (7) After the step 4 is completed, the temperature is kept for a certain period of time, and the temperature is controlled. After the temperature is kept, the temperature is lowered, and the above-mentioned oxidant is added. After stirring, the above-mentioned reducing agent is added. After stirring, the temperature is continued to be lowered to 45° C., and the material is discharged.

Citation Information

Patent Citations

  • Packaging material based on biodegradation technology

    CN113136055A

  • Removable acrylate pressure-sensitive adhesive with high peel strength and preparation method thereof

    CN115537155A